واقع التصنيع في الجزائر - سمية, لعرامي; كريمة, خزان (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة الى تحديد أثر القطاع الصناعي على النمو الاقتصادي في الجزائر للفترة (1995-2021)، بالاعتماد على منهجية حديثة متمثلة في نموذج الانحدار الذاتي للإبطاء الزمني الموزع (ARDL) لتقدير العلاقة في المدى القصير والطويل، حيث تم اتخاذ الناتج المحلي الإجمالي ممثل للنمو الاقتصادي كمتغير تابع، والصناعات التحويلية والاستخراجية كمتغيرات مستقلة، وتوصلت الدراسة إلى أن حجم الصناعة الاستخراجية أكبر من حجم الصناعة التحويلية لكن تأثير الصناعة التحويلية أكبر من تأثير الصناعة الاستخراجية، ويمكن لهذا الأثر أن يصبح أكثر فعالية على النمو الاقتصادي وذلك بالتقليل من الاعتماد بصورة أكبر على الصناعة الاستخراجية لأنها عرضة لصدمات أسعار النفط والتقلبات الخارجية . This study aimed to determine the impact of the industrial sector on economic growth in algeria for the period (1995-2021) ، Based on a modern methodology represented by the ARDL autoregressive distributed time delay model to estimate the relationship in the short and long term،Where the gross domestic product was taken as a representative of economic growth as a dependent variable ،manufacturing and extractive industries as independent variables ،the study concluded that the size of the extractive industry is greater than the size of the manufacturing industry،but the impact of the manufacturing industry is greater that the impact of the extractive industry . this effect can become more effective on economic growth by reducing dependence more on the extractive industry because it is vulnerable to oil price shocks and external fluctuations.
Keywords: صناعة تحويلية-صناعة استخراجية-نمو اقتصادي-ناتج محلي إجمالي-ARDL; manufacturing industry- extractive industry- economic growth- gross domestic product- ARDL